The Influence of Customer Value Chain Analysis on Customer Satisfaction. A Case of Banking in the Emerging Country (Global Journal of Management and Business Research, 2019)
The realization customer -value analysis is likely to emerge as a contemporary model for improvement of customer relationship management within the banking industry. This means that the cost of acquiring customer base has become expensive and organisations have developed strategies to create customer loyalty. The strategies that have been employed by organisations is to improve customer service provision through is through activity analysis. Activity analysis have been cited as a driver of superior services and a driver of customer satisfaction. It is in this light that this study the impact of Customer Value Chain Analysis on Customer Satisfaction in a selected a bank in a banking industry. A qualitative was used in this study where a phenomenological research philosophy was adopted to answer the research problem and primary research findings were gathered from 10 managerial employees of the selected bank within the banking industry. The research sample was selected using purposive sampling technique and the findings were analysed thematically.